2008
DOI: 10.4296/cwrj3302181
|View full text |Cite
|
Sign up to set email alerts
|

Low-Flows in Deterministic Modelling: A Brief Review

Abstract: Deterministic hydrological models are limited in their ability to model low-flows, but as they are increasingly being used for low-flow studies, a review is timely if they are to be used for this purpose. The representations of the physical processes that govern low-flows are described for a selection of models developed and/or used in Canada. The models vary in the extent to which they incorporate low-flow processes, such as drawdown of storage in lakes, stream channels and wetlands, riparian evapotranspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
1
8
0
1
Order By: Relevance
“…They concluded that it was difficult to quantify this impact because of a lack of understanding of the relationship between flow and fish populations as well as spatio-temporal stream biota respond to habitat changes. Useful information on characteristics and variability of low flows can also be found in Davison and van der Kamp (2008), Ouarda et al (2008), Whitfield (2008), Smakhtin (2001) and Barnett et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that it was difficult to quantify this impact because of a lack of understanding of the relationship between flow and fish populations as well as spatio-temporal stream biota respond to habitat changes. Useful information on characteristics and variability of low flows can also be found in Davison and van der Kamp (2008), Ouarda et al (2008), Whitfield (2008), Smakhtin (2001) and Barnett et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…A hydrological model integrates these physical factors that interact with climate and influence the movement of water (e.g., infiltration, evaporation etc.). Modelling of low flows using deterministic hydrological models is greatly determined by the extent to which low flow processes such as evapotranspiration, freeze-up, drawdown of storage in lakes, stream channels and wetlands are incorporated (Davison and Kamp 2008). These processes operate over a wide range of spatial and temporal scales.…”
Section: Comparison Between Dd Id and Pva Approachesmentioning
confidence: 99%
“…Therefore, representing the associated processes with constant (e.g., melt rate during a rain period) or monthly varying (e.g., rainfall intensity versus percent effectiveness evapotranspiration index (PETI), monthly PETI, monthly percent effective melt rate) values may limit the ability of SSARR to represent low flow governing processes. In a review by Davison and Kamp (2008) on low flows in deterministic modelling, six hydrological models (HBV, WATFLOOD, UBCWM, GAWSER, HYDROTEL, VIC, CRHM) were reviewed in terms of their ability to model low flows. As with the SSARR model, it was concluded that considerable work remains to be done in the adequate representation of low flow processes and in the evaluation of both lumped and distributed models.…”
Section: Comparison Between Dd Id and Pva Approachesmentioning
confidence: 99%
“…Ces travaux se sont intéressés à plusieurs aspects dont l'analyse des facteurs et processus de genèse des débits minimums, ainsi que l'élaboration des indices pour définir les caractéristiques des débits minimums annuels (DRACUP et al, 1980;GURNELL, 1993;GUSTARD et IRVING, 1994;HOPKINSON et YOUNG, 1998;SMAKHTIN, 2001;YUNUS et al, 2003). Par ailleurs, plusieurs autres études se sont intéressées à l'estimation, à la prédiction et à la modélisation des débits minimums annuels (ABI-ZEID et BOBÉE, 1999;DAVISON et VAN DER KAMP, 2008;HEJAZI et MOGLEN, 2006;ONOZ et BAYAZIT, 2002;OUARDA et al, 2008;YUREKLI et OZTURK, 2003), afin de pouvoir définir les normes des débits réservés qui ont une importance capitale pour la protection de l'intégrité écologique des habitats aquatiques (ANNEAR et CONDOR, 1984;MUNSON et DELFINO, 2007;PETTS, 1995;SCATENA, 2004;VISMARA et al, 2001). C'est dans ce contexte que de nombreuses études ont été réalisées pour analyser les effets d'activités anthropiques (barrages hydroélectriques en particulier) sur les débits minimums (ASSANI et al, 2005;HU et al, 2008;MAGILLAN et NISLOW, 2001PYRON et NEUMANN, 2008;YANG et al, 2008).…”
Section: Introductionunclassified